GRAFFITI CHANGE IN A DECADE, BECOME A COMMERCIAL COMMODITY IN THE CITY OF SURABAYA - Aryo Bayu Wibisono; Ryan Rizki Herdianto (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2018)
Commodity Graffiti is the art of the streets that adorned cities in the modern era. Graffiti is a culture that cannot be separated from the role of human communal in certain areas, in addition to show on the group existence , graffiti often perceived as markers an epoch. Graffiti but is no longer owned by groups that feel they own the art of course, Graffiti develops into a medium that transformed and give oasis in urban cities Surabaya. Research with the title œChange Graffiti On a decade, into a Commercial Commodity in the city of Surabaya will break down how and what factors make Graffiti in the era of modernity is now turned towards the commercial. Research method used to unravel Graffiti changes in Surabaya first with the observation field technique to Graffiti artist or advertisers, second analysis of interviews with Graffiti stakeholders and the last book, literature journals as well as the media as secondary data research to supporting.